2003
DOI: 10.1001/archderm.139.9.1149
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Prognosis of Idiopathic Solar Urticaria

Abstract: Background: As little has been published on the course of idiopathic solar urticaria (SU) patients cannot receive comprehensive prognostic advice. Objective: To determine the prognosis and photobiological characteristics of idiopathic SU. Design: Historical cohort study, with inception cohort followed up from time of diagnosis. Follow-up for a median of 4 years (range, 3 months to 26 years) after diagnosis. Setting: Tertiary referral center for the investigation of photodermatoses in Scotland. Patients: The st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
113
3
25

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 144 publications
(148 citation statements)
references
References 29 publications
7
113
3
25
Order By: Relevance
“…On the other hand, fluorescent lamps are associated with certain health effect as headache and fatigue caused by harmonics generated by the lamp and induces disease activity among individuals with pathological sensitivity to ultraviolet light. In rare cases some persons can get rash from fluorescent lamps (Colman et al, 1976;Binnie, 1979;Rihner & McGrath, 1992;Küller & Laike, 1998;Beattie et al, 2003). It is also thought that patients with conditions such as xeroderma, pigmentosun, lupus migraine, epilepsy, myalgic and autism could be aggravated by flicker and /or UV/blue light (especially UVB and UVC) (Millard & Hawk, 2001;SCENIHR, 2008).…”
Section: Environmental Impact and Safety Of Ssl-ledmentioning
confidence: 99%
“…On the other hand, fluorescent lamps are associated with certain health effect as headache and fatigue caused by harmonics generated by the lamp and induces disease activity among individuals with pathological sensitivity to ultraviolet light. In rare cases some persons can get rash from fluorescent lamps (Colman et al, 1976;Binnie, 1979;Rihner & McGrath, 1992;Küller & Laike, 1998;Beattie et al, 2003). It is also thought that patients with conditions such as xeroderma, pigmentosun, lupus migraine, epilepsy, myalgic and autism could be aggravated by flicker and /or UV/blue light (especially UVB and UVC) (Millard & Hawk, 2001;SCENIHR, 2008).…”
Section: Environmental Impact and Safety Of Ssl-ledmentioning
confidence: 99%
“…Most patients react to more than one wavelength group, with a greater proportion sensitive to UV-A and short visible wavelengths. 1 The clinical picture involves erythema and wheal formation with itch, most commonly after minutes of exposure to the pathogenic wavelengths, followed by fading of the reaction within a few hours. The severity of the symptoms varies tremendously, however, between patients and within each patient at various time points.…”
mentioning
confidence: 99%
“…2 The course of idiopathic solar urticaria is usually long-term. In a comprehensive historical cohort study, 1 it was shown that clinical resolution occurred in 12%, 26%, and 36% of patients 5, 10, and 15 years after diagnosis, respectively, with another third showing clinical improvement with time. Approximately onequarter of the patients had the coexistence of other photodermatoses, primarily polymorphic light eruption, worsening the prognosis of the disease.…”
mentioning
confidence: 99%
See 2 more Smart Citations